Сталий розвиток аграрних підприємств в Україні - Лема, О. І.; Матковський, О. А.; Коваль, О. Р.; Сярий, І. В.; Lema, O. I.; Matkovskyi, O. A.; Koval, O. R.; Siaryi, I. V. (Видавництво Львівської політехніки, 2023)
Статтю присвячено дослідженню стану та перспективам впровадження концепції сталого розвитку в діяльність аграрних підприємств в Україні. Розглянуто концепцію сталого розвитку та її складові, зокрема, цілі сталого розвитку та механізми мотивування впровадження концепції сталого розвитку у діяльність підприємств. Визначено ресурсні, економічні, правові та соціальні фактори впливу на розвиток аграрних підприємств в Україні. Розроблено рекомендації для держави та аграрних підприємств стосовно дій для впровадження у свою діяльність концепції сталого розвитку та досягнення цілей сталого розвитку.

The article is devoted to the study of the state and prospects of the implementation of the concept of sustainable development in the activities of agricultural enterprises in Ukraine. The article examines the concept of sustainable development and itscomponents, in particular the Sustainable Development Goals and mechanisms of implementation of the concept of sustainable development in the activities of enterprises. The resource, economic, legal and social factors influencing the development of agricultural enterprises in Ukraine are determined. Recommendations have been developed for the state and agricultural enterprises regarding actions to implement the concept of sustainable development in their activities and achieve the goals of sustainable development. The agricultural sector in Ukraine is relatively nascent, having commenced its comprehensive formation approximately three decades ago. Presently, a majority of agricultural entities find themselves in a phase marked by the expansion of operations and the augmentation of capital assets. This circumstance affords an opportunity wherein the entire industry may be structured in accordance with the tenets of sustainable development. Such an approach is poised not only to bolster the economic resilience of enterprises but also to ameliorate environmental conditions and enhance the overall welfare of the populace. Consequently, there arises a necessity to undertake an exhaustive examination aimed at discerning the contemporary status and distinctive features characterizing the evolution of agricultural enterprises in Ukraine. This examination should yield recommendations, particularly for governmental entities, delineating potential measures for the integration of sustainable development principles into the operational frameworks of agricultural enterprises. Today, most agricultural enterprises are at the stage of expansion of activities and development of capital assets. This creates conditions when the entire industry can be built on the principles of sustainable development, which will ensure not only the economic stability of enterprises, but also improve the state of ecology and the well-being of the population. In view of this, it becomes necessary to carry out a detailed study to determine the current state and characteristics of the development of agricultural enterprises in Ukraine, to develop recommendations, in particular for the state, regarding potential steps for introducing the concept of sustainable development into the activities of agricultural enterprises.
Sustainable development of agricultural enterprises in Ukraine
Keywords: сталий розвиток; аграрні підприємства; аграрна галузь; цілі сталого розвитку; sustainable development; agrarian enterprises; agrarian industry; Goals of sustainable development; 658; 005